Saliva: an important alternative for screening and monitoring of COVID-19 in children - Santos,Catielma Nascimento (2020)
Abstract: The increasing number of cases of COVID-19 worldwide poses challenges to healthcare systems not only in effectively identifying individuals positive for SARS-CoV-2, but also in isolating cases to minimise contagion in early diagnosing more severe cases that will need hospitalization. Less-invasive collection methods are indispensable in a pandemic scenario as large-scale tests are necessary to understand the actual evolution of contagion in different populations, thus enabling decision-making based on scientific evidence. Saliva has been shown to be an alternative for diagnosing viral infections as this biological fluid can be easily and quickly collected without using specific devices and causing less discomfort during collection, which is an important factor for use in children. Despite the smaller percentage of severe cases of COVID-19 among children, they seem to play an important role in the contagion as they have the same potential of transmission as that of adults. Knowing the evolution of COVID-19 pandemic in children is extremely important, mainly regarding the changing in rules of social distancing, such as re-opening schools and recreational activities spaces. In addition, countless cases of a severe multi-systemic inflammatory syndrome that shares clinical and laboratory features with Kawasaki's disease have been recently related to SARS-CoV-2 infections in children, adolescents and young adults. In view of this scenario, the aim of this study was to present saliva as an alternative for seeking diagnostic and prognostic markers of COVID-19 in children, including adequate sample collection techniques for different age groups.